Two sides of one coin: massive hepatic necrosis and progenitor cell-mediated regeneration in acute liver failure - Weng, Hong-Lei; Cai, Xiaobo; Yuan, Xiaodong; Liebe, Roman; Dooley, Steven; Li, Hai; Wang, Tai-Ling (Frontiers in Physiology, 2015)
Massive hepatic necrosis is a key event underlying acute liver failure, a serious clinical syndrome with high mortality. Massive hepatic necrosis in acute liver failure has unique pathophysiological characteristics including extremely rapid parenchymal cell death and removal. On the other hand, massive necrosis rapidly induces the activation of liver progenitor cells, the so-called “second pathway of liver regeneration”. The final clinical outcome of acute liver failure depends on whether liver progenitor cell-mediated regeneration can efficiently restore parenchymal mass and function within a short time. This review summarizes the current knowledge regarding massive hepatic necrosis and liver progenitor cell-mediated regeneration in patients with acute liver failure, the two sides of one coin.